Macroeconomic Factors Affecting Poverty in Central Java (2018–2023): Post-Pandemic Challenges and Inclusive Growth Perspective - Tiara Rizky Zein Muhammad; Retno Febriyastuti Widyawati (Pattimura University, 2026)
This study analyzes the influence of macroeconomic variables on poverty levels in Central Java Province during the 2018–2023 period, which captures the pre-pandemic, pandemic, and post-pandemic phases. Using panel data from 34 regencies/cities and employing a Fixed Effect Model (FEM), this research examines the effects of the open unemployment rate (TPT), minimum wage, Human Development Index (HDI), and Gross Regional Domestic Product (GRDP) on poverty. The results show that TPT does not have a significant effect on poverty, while minimum wage has a positive and significant effect, and HDI and GRDP have significant negative effects on poverty. These findings indicate that improvements in human development and inclusive economic growth are crucial for poverty reduction, while minimum wage policies may generate unintended short-term effects, particularly in regions dominated by informal employment. This study contributes by highlighting post-pandemic regional dynamics and the importance of inclusive development strategies in addressing poverty under conditions of economic uncertainty.